Recensiones - Varios, Autores (MHNH. Revista Internacional de Investigación sobre Magia y Astrología Antiguas, 2018)
Theophilus of Edessa, Astrological Works. Labors Concerning Military Inceptions, On Cosmic Inceptios, Apotelesmatics, On Various Inceptions. The Arabic passages. Translated by Eduardo J. Gramaglia. Edited with an introduction by Benjamin N. Dykes, Minneapolis, Minnesota, The Cazimi Press, 2017, VIII+334 pp. [ISBN: 978-1-934586-45-7] (Aurelio Pérez Jiménez) Ab? Ma?šar (Albumasar), La Piccola Introduzione alla scienza degli astri. Introduzione, traduzione del testo arabo e note di Franco Martorello. Agora & CO, Roma, 2018, 220 pp. [ISBN: 888952619X & 9788889526194] (Hilario Bautista)